2023
DOI: 10.2169/internalmedicine.1372-22
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis Type 1 with a Giant Diffuse Plexiform Neurofibroma Invading the Liver

Abstract: Plexiform neurofibromas (PNs) occur in approximately 50% of patients with neurofibromatosis type 1 (NF 1). PNs are rare in the abdominal cavity and especially rare in hepatobiliary lesions. A 31-year-old man with NF1 had a tumor extending along the celiac artery, superior mesenteric artery, and intrahepatic portal vein. We diagnosed him with diffuse PN based on liver tumor biopsy findings and the tumor form. Because the tumor had invaded along the intrahepatic portal vein, surgical resection was deemed difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Studies have shown that PNs can also transform into malignant peripheral nerve sheath tumors in almost 10% of patients. [ 26 27 28 ] The mechanism of action of selumetinib in NF-1-associated PNs is similar to that of cancer, i.e., inhibition of MEK1/2, the upstream kinases that activate ERK1/2, which is an effector in the RAS-MAPK pathway. Inhibition of MEK1/2 by selumetinib leads to interference in the RAS-MAPK pathway activation, which contributes to reduced tumor growth in NF-1-associated PNs.…”
Section: Clinical Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that PNs can also transform into malignant peripheral nerve sheath tumors in almost 10% of patients. [ 26 27 28 ] The mechanism of action of selumetinib in NF-1-associated PNs is similar to that of cancer, i.e., inhibition of MEK1/2, the upstream kinases that activate ERK1/2, which is an effector in the RAS-MAPK pathway. Inhibition of MEK1/2 by selumetinib leads to interference in the RAS-MAPK pathway activation, which contributes to reduced tumor growth in NF-1-associated PNs.…”
Section: Clinical Usesmentioning
confidence: 99%
“…Studies have shown that PNs can also transform into malignant peripheral nerve sheath tumors in almost 10% of patients. [ 26 27 28 ]…”
Section: Clinical Usesmentioning
confidence: 99%